The Influence of 24-h Ambulatory Blood Pressure on Cognitive Function and Neuropathological Biomarker in Patients With Alzheimer's Disease - Li, Lixia; Wang, Weijia; Lian, Tenghong; Guo, Peng; He, Mingyue; Zhang, Weijiao; Li, Jinghui; Guan, Huiying; Luo, Dongmei; Zhang, Weijia; Zhang, Wei (Frontiers in Aging Neuroscience, 2022)
Purpose: This study aimed to investigate the influence of 24-hour ambulatory blood pressure (BP) on cognitive function and neuropathological biomarkers in patients with Alzheimer's disease (AD) at stages of mild cognitive impairment (MCI) and dementia. Method: AD patients were divided into MCI (AD-MCI) group and dementia (AD-D) group. 24-hour BP variables, including BP level, coefficient of variation (CV) of BP, and pulse pressure were collected and compared between the two groups. The correlations between 24-hour BP variables and the scores of cognitive domains were analyzed. The independent influencing factors of cognitive domains of AD patients were investigated. The levels of neuropathological biomarkers, including β amyloid (Aβ)1-42, phosphorylated tau protein (P-tau) and total tau (T-tau), in CSF were measured and compared between the two groups, and the correlations between 24-hour BP variables and the levels of neuropathological biomarkers of AD were analyzed. Results: Daytime CV of systolic BP (SBP) was significantly increased in AD-D group comparing to that in AD-MCI group. The 24-hour and daytime CV of SBP and ambulatory pulse pressure were significantly and negatively correlated with memory score. The average 24-hour and average daytime SBP level and CV of SBP, daytime CV of diastolic BP, and 24-hour, daytime and night-time ambulatory pulse pressure were significantly and negatively correlated with language score. The average 24-hour SBP level, daytime CV of SBP, and 24-hour, daytime and night-time ambulatory pulse pressure were significantly and negatively correlated with attention score. Further analysis indicated that daytime CV of SBP as well as age and course of disease were the independent influencing factor of language. Age was also the independent influencing factor of memory and attention of AD patients. T-tau level in CSF in AD-D group was significantly higher than that in AD-MCI group, but the levels of Aβ1-42, P-tau and T-tau in CSF were not correlated with 24-hour ambulatory BP variables. Conclusion: Daytime CV of SBP was the independent influencing factor of language in AD patients. AD-D patients had significantly severer neurodegeneration than AD-MCI patients, which was however not through the influence of 24-hour ambulatory BP variables on neuropathological biomarkers of AD.